2001
DOI: 10.1002/bies.1097
|View full text |Cite
|
Sign up to set email alerts
|

The CtBP family: enigmatic and enzymatic transcriptional co‐repressors

Abstract: Transcription factors that associate with DNA sequences in promoters and enhancers often recruit co-regulators that modulate their activity. Many of these co-regulators have intrinsic enzymatic activity and influence gene expression by modifying chromatin and altering its structure. Recently, a new family of co-repressors, the C-terminal binding proteins, has been described. These proteins recognize Pro-X-Asp-Leu-Ser (PXDLS) motifs in DNA-binding proteins and function as transcriptional co-repressors in Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
166
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(174 citation statements)
references
References 56 publications
4
166
0
1
Order By: Relevance
“…Histone deacetylases as well as Polycomb proteins can induce modifications of the nucleosomal organization (14,15). We considered the possibility that our inability to show a CtBP-dependent repression of the E-cadherin promoter by SIP1 could be due to the use of reporter plasmids.…”
Section: ␦Ef1 and Ctbp-dependent Repression Of E-cadherin-mentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylases as well as Polycomb proteins can induce modifications of the nucleosomal organization (14,15). We considered the possibility that our inability to show a CtBP-dependent repression of the E-cadherin promoter by SIP1 could be due to the use of reporter plasmids.…”
Section: ␦Ef1 and Ctbp-dependent Repression Of E-cadherin-mentioning
confidence: 99%
“…In the case of the E-cadherin promoter and its regulation by ␦EF1, the corepressor C-terminal binding protein (CtBP) was proposed to be necessary for transcriptional repression (10). CtBP was originally identified as a protein that interacts with the C-terminal segment of the adenovirus E1A oncoprotein via a PLDLS sequence in the latter (13), and interacts with a growing list of transcription factors from Drosophila and vertebrates (14,15). Two highly related CtBP proteins, CtBP1 and CtBP2, have been identified in vertebrates and have overlapping but also unique roles during embryogenesis, as shown by loss-of-function studies in the mouse (16).…”
mentioning
confidence: 99%
“…Although not identified in previous studies, recent reports found a weak dehydrogenase activity associated with CtBP (Kumar et al, 2002;Balasubramanian et al, 2003;Shi et al, 2003). CtBP has been found to bind directly to histone deacetylases (HDACs), suggesting that the corepressor may effect repression by chromatin remodeling (reviewed by Turner and Crossley, 2001;Chinnadurai, 2002). A recent biochemical purification of CtBP identified additional proteins in a complex, including histone methyltransferases, the CoREST repressor and a protein homologous to polyamine oxidases (Shi et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Transcription factors typically bind to CtBP via a short peptide motif similar to the PLDLS sequence originally identified in E1A (Schaeper et al, 1995). CtBP is homologous to α-hydroxyacid dehydrogenases, and contains a conserved NADbinding domain as well as conserved residues in the putative active site (reviewed by Chinnadurai, 2002;Turner and Crossley, 2001). Although not identified in previous studies, recent reports found a weak dehydrogenase activity associated with CtBP (Kumar et al, 2002;Balasubramanian et al, 2003;Shi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of the C-terminal region of AdE1A reduces the frequency of transformation by AdE1A together with AdE1B, but increases the frequency of transformation by AdE1A and activated ras (Douglas et al, 1991;Subramanian et al, 1989Subramanian et al, , 1991. CtBP has been shown to interact with a large number of mammalian transcriptional repressors, such as BKLF, Ikaros, Net and the Drosophila repressors Snail, Hairy and Knirps as well as histone deacetylases (HDACs) (reviewed by Turner and Crossley, 2001;Chinnadurai, 2002Chinnadurai, , 2004Chinnadurai, , 2006aChinnadurai, , 2007.…”
Section: Introductionmentioning
confidence: 99%